2014
DOI: 10.1007/s10047-014-0796-7
|View full text |Cite
|
Sign up to set email alerts
|

Implantation study of a tissue-engineered self-expanding aortic stent graft (bio stent graft) in a beagle model

Abstract: The use of stent grafts for endovascular aortic repair has become an important treatment option for aortic aneurysms requiring surgery. This treatment has achieved excellent outcomes; however, problems like type 1 endoleaks and stent graft migration remain. Bio stent grafts (BSGs), which are self-expanding stents covered with connective tissue, were previously developed using "in-body tissue architecture" technology. We assessed their early adaptation to the aorta after transcatheter implantation in a beagle m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Indeed, in our previous studies [3], we discovered that high-frequency EF stimulation results in activation of vascular endothelial cells and angiogenic cell responses via the mechanism consistent with the model presented above. The results of the present study, therefore, may lead to the development of new approaches for vascular stents, where endothelial cell activation, proliferation and migration can be the key factor that determines success or failure of the stent [79,80].…”
Section: Physiological Implicationsmentioning
confidence: 83%
“…Indeed, in our previous studies [3], we discovered that high-frequency EF stimulation results in activation of vascular endothelial cells and angiogenic cell responses via the mechanism consistent with the model presented above. The results of the present study, therefore, may lead to the development of new approaches for vascular stents, where endothelial cell activation, proliferation and migration can be the key factor that determines success or failure of the stent [79,80].…”
Section: Physiological Implicationsmentioning
confidence: 83%
“…Some papers have reported that biosheets based on iBTA can be reconstructed in a manner analogous to that of native tissue, for example, as cornea, trachea (biosheet), and blood vessels (biotube) [8,9]. The technology based on iBTA have also been applied to heart valves (biovalve and stent-biovalve) [10,11] and stent grafts (bio stent graft) [12]. The papers that reported on this technology indicated the possibility of tissue regeneration, self-repair, and growth adaptability.…”
Section: Discussionmentioning
confidence: 99%
“…BioSGs are composed of a metallic stent sandwiched or attached to a TEVG, aimed to improve postoperative outcomes (e.g., no risk of graft infection or aortoenteric fistula developing, and antithrombogenicity from early endothelialization). [99][100][101] To enhance the overall sealing performance, a unique graft system was developed [99] by compounding degradable polyglycolide (PGA, core) and nondegradable PET (sheath) fibers (Figure 5a). This configuration encouraged tissue ingrowth from the aortic wall into the graft fabric, where late migration and endoleak postdeployment were effectively avoided.…”
Section: Bioengineered Stent-grafts (Biosgs)mentioning
confidence: 99%
“…BioSGs are composed of a metallic stent sandwiched or attached to a TEVG, aimed to improve postoperative outcomes (e.g., no risk of graft infection or aortoenteric fistula developing, and anti‐thrombogenicity from early endothelialization). [ 99–101 ]…”
Section: Current State‐of‐the‐artmentioning
confidence: 99%
See 1 more Smart Citation